PENGARUH KOMUNIKASI INTERPERSONAL TERHADAP KINERJA PEGAWAI PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN GOWA - fahruni khaerunnisa; Yayu Rakkang (Prodi Manajemen Universitas Syekh Yusuf Al Makassari Gowa, 2025)
This study aims to determine the influence of interpersonal communication on employee performance at the Department of Industry and Trade of Gowa Regency. Interpersonal communication is an essential element in creating a productive and harmonious work environment, which directly impacts the effectiveness of employee performance. This research employs a quantitative approach using a descriptive method. The sample consisted of 37 respondents, representing the entire staff of the institution, selected through a saturated sampling method. The data analysis technique used is simple linear regression. The results indicate that interpersonal communication has a positive and significant effect on employee performance. This is evidenced by a significance value of 0.001 (< 0.05) and a coefficient of determination (R²) of 0.285, meaning that interpersonal communication explains 28.5% of the variation in employee performance. These findings reinforce the importance of interpersonal communication in improving work quality, productivity, and interpersonal relationships among employees in government organizations. Therefore, strengthening interpersonal communication is recommended as a strategy to enhance employee performance.